Solve for y -6(y+8)-44=5-43

Math
-6(y+8)-44=5-43
Simplify -6(y+8)-44.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-6y-6⋅8-44=5-43
Multiply -6 by 8.
-6y-48-44=5-43
-6y-48-44=5-43
Subtract 44 from -48.
-6y-92=5-43
-6y-92=5-43
Subtract 43 from 5.
-6y-92=-38
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 92 to both sides of the equation.
-6y=-38+92
Add -38 and 92.
-6y=54
-6y=54
Divide each term by -6 and simplify.
Tap for more steps…
Divide each term in -6y=54 by -6.
-6y-6=54-6
Cancel the common factor of -6.
Tap for more steps…
Cancel the common factor.
-6y-6=54-6
Divide y by 1.
y=54-6
y=54-6
Divide 54 by -6.
y=-9
y=-9
Solve for y -6(y+8)-44=5-43

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top